Silica Nanoparticles Effects on Blood Coagulation Proteins and Platelets - Volodymyr Gryshchuk; Natalya Galagan (Biochemistry Research International)
Interaction of nanoparticles with the blood coagulation is important prior to their using as the drug carriers or therapeutic agents. The aim of present work was studying of the primary effects of silica nanoparticles (SiNPs) on haemostasis in vitro. We studied the effect of SiNPs on blood coagulation directly estimating the activation of prothrombin and factor X and to verify any possible effect of SiNPs on human platelets. It was shown that SiNPs shortened coagulation time in APTT and PT tests and increased the activation of factor X induced by RVV possibly due to the sorption of intrinsic pathway factors on their surface. SiNPs inhibited the aggregation of platelet rich plasma induced by ADP but in the same time partially activated platelets as it was shown using flow cytometry. The possibility of SiNPs usage in nanomedicine is strongly dependant on their final concentration in bloodstream and the size of the particles that are used. However SiNPs are extremely promising as the haemostatic agents for preventing the blood loss after damage.